Active noise control for air handling unit - Low, Cher Wee. (2008)
This dissertation is focused on the development of an active noise control (ANC) system for air handling unit comprising of a Heating, Ventilating, Air Conditioning (HVAC) duct and a motor driven blower. The objective is to devise feasible algorithms in reducing noises induced by the fan within the Air Handling Unit (AHU).